Correlation of A Mating Type with Mycelial Growth Rate in Basidiospore-derived Monokaryons of Lentinula edodes - Mi-Jeong Park; Rhim Ryoo; Yeongseon Jang; Kang-Hyeon Ka (한국균학회지, 2021)
Lentinula edodes is a tetrapolar basidiomycete and its mating type is determined by two unlinked genetic loci, A and B. Theoretically, one dikaryotic strain could produce basidiospores with four different mating types in a 1:1:1:1 ratio. Previous studies have described the skewed segregation ratio of mating types among basidiospores of L. edodes. However, they were based only on morphological characteristics, such as clamp connection, to determine mating types. To clarify whether the segregation distortion of mating types is a general phenomenon in L. edodes, we analyzed the mating types of basidiospores obtained from three cultivars of L. edodes using recently developed DNA markers. We found that the skewed segregation of mating types was strain-specific, as reported previously. Among the three cultivars, one cultivar showed balanced segregation, while the other two displayed distorted segregation. We also examined the relationship between mating type and mycelial growth rate of monokaryons derived from each basidiospore. It was found that the monokaryotic mycelial growth rate was related to the A mating type but not to the B mating type. Therefore, homeodomain transcription factor genes that reside on the A locus or other genes linked to the A locus affect the growth rate of monokaryotic mycelia. Considering the importance of mating types in mushroom breeding, this study is informative for establishing an efficient breeding strategy as well as for understanding the mechanism of monokaryotic mycelial growth.